KOMUNIKASI PEMBANGUNAN DAN TOLERANSI ANTAR PERBEDAAN - Hamdan, Hamdan (Universitas Islam Negeri Mataram, 2017)
Development communication is the idea that aims to create community compounds and strives to involve all groups in the development of physical and non physical. Development communication in the context of Indonesia is very important to build up a tolerance and harmony between fellow in social interaction-interaction community. Indonesia is one of the countries most compounds in the world, it can be seen in terms of ethnicity, language and religion. In development, communication and tolerance of differences in question here is not only communication leads to physical development, but development that leads to the kognif aspect as well. Because in the society development communication is not the focus of the compound cuukup just on spec development physically, but the most important is the communication that leads to the builders of the spirit of tolerance of antarperbedaan with the aim of getting the harmony of the nation and State. Such things can be achieved by identifying the values and rules that are stored on each of these differences in order to influence society with all of the differences, both accommodate differences in aspects of religion, culture and politics.